Attitudes of English majors towards the use of the Quizizz platform in English language learning - Nga Thi Tuyet Phan (Ho Chi Minh City Open University Journal of Science - Social Sciences)
This mixed-methods study explores the attitudes of English majors towards the use of Quizizz in their English language learning and examines variations in these attitudes based on gender and English proficiency levels. The study included 200 English majors from a Vietnamese university who responded to questionnaires. Fifteen students consented to participate in focus group discussions, representing each year of the study program. In contrast to previous research, this study revealed that participants expressed negative attitudes toward the use of Quizizz, as they did not find it beneficial or useful for their learning. There were no significant differences in students’ attitudes, including affective, behavioral, and cognitive components, towards the use of Quizizz across different demographic variables. This study provides several recommendations for the effective utilization of Quizizz in EFL (English as a Foreign Language) classrooms. It also underscores the need for further research to investigate the correlation between English majors’ attitudes toward Quizizz and other relevant factors in EFL settings.